ACEH LOCAL WISDOM IN THE METHOD OF DETERMINING THE HIJRI CALENDAR - Hasna Tuddar Putri; Ibnu Qodir (Al-Hilal: Journal of Islamic Astronomy, 2022)
Calendars with cultural nuances are part of local wisdom that should be preserved, one of which is the formulation of Sheikh Abbas Kutakarang's calendar from Aceh. This article aims to see how Sheikh Abbas Kutakarang shaped local wisdom in the method of determining the classical Hijri calendar in Aceh. This article is qualitative in nature by using library data with content analysis method. The primary data source used is the book of Tāj al-Mulūk by Sheikh Abbas Kutakarang. This article finds that there are characteristics of local wisdom in determining the classical Hijri calendar in Aceh in different methods and algorithms from classical Javanese reckoning. These differences have an impact on differences in determining the beginning of the Hijri year. This method is a representation of local wisdom in the Hijri calendar in Aceh.